Evaluation of The Drainage System for Handling Flooding Floods in Villa Ciomas Indah Area, Ciomas Rahayu Village, Ciomas District, Bogor Regency - Afifah, Jihan; Daryati, Daryati; Maulana, Arris (Journal of Engineering Education and Pedagogy, 2023)
This study aims to evaluate the capacity of drainage channels in dealing with flooding puddles. This study used the calculations of hydrology analysis and hydraulic analysis to find out the capacity of flooding and debit. Research instruments use documentation in the form of archives are obtained from government offices by collecting primary data and secondary data. Data analysis uses comparative deskritif quantitative t-shirt analysis. The results showed that the conduit capacity (Qsal) that its cross-sectional form and used stone partners with a wide size of the channel (B) 80 cm and the depth of the channel (h) 70 cm can not accommodate a 10-year flood debit plan, so an evaluation was carried out to be 100 cm × 100 cm.